2022
DOI: 10.1007/s11626-022-00648-z
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin attenuates dimethyl sulfoxide– and Zika virus–induced degeneration of porcine induced neural stem cells

Abstract: Domestic pigs have become increasingly popular as a model for human diseases such as neurological diseases. Drug discovery platforms have increasingly been used to identify novel compounds that combat neurodegeneration. Currently, bioactive molecules such as melatonin have been demonstrated to offer a neuroprotective effect in several studies. However, a neurodegenerative platform to study novel compounds in a porcine model has not been fully established. In this study, characterized porcine induced neural ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…With the aid of a molecular docking technique, the authors also showed that melatonin had a high binding affinity to the nonstructural protein (NS3) of the virus; this may be a mechanism by which melatonin inhibits the Zika infection. The second report documented that melatonin reduced degeneration and death of porcine neural stem cells 23 . Since there is no specific treatment for a Zika infection, the information summarised here may be useful in reducing the severity of this disease.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…With the aid of a molecular docking technique, the authors also showed that melatonin had a high binding affinity to the nonstructural protein (NS3) of the virus; this may be a mechanism by which melatonin inhibits the Zika infection. The second report documented that melatonin reduced degeneration and death of porcine neural stem cells 23 . Since there is no specific treatment for a Zika infection, the information summarised here may be useful in reducing the severity of this disease.…”
Section: Resultsmentioning
confidence: 89%
“…The second report documented that melatonin reduced degeneration and death of porcine neural stem cells. 23 Since there is no specific treatment for a Zika infection, the information summarised here may be useful in reducing the severity of this disease.…”
Section: High Riskmentioning
confidence: 99%